1978
DOI: 10.1530/jrf.0.0520051
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gonadotrophins and oestradiol during oestrus in the cow

Abstract: Summary. LH values between \ m=-\ 2 and +4 h (0 h =LH peak) were higher than baseline.FSH values were also raised at this time and between + 16 and + 30h. Oestradiol values between \m=-\20 and 0 h were higher than during + 4 to + 20h.Plasma FSH levels during the bovine oestrous cycle have been measured (Akbar, Reichert, Dunn, Kaltenbach & Niswender, 1974; Deri vaux, Ectors, Hendrick & Franchimont, 1974;Schams & Schallenberger, 1976), but details of the changes in plasma oestradiol concentration and those of LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
25
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 5 publications
9
25
0
Order By: Relevance
“…Buffaloes 9-13 conceived but Buffalo 14 did not. (1977,1978) and Dobson (1978) (1976) and has also been found in cattle (Snook et al, 1971): it is thought to be correlated with growth and atresia of anovulatory follicles.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Buffaloes 9-13 conceived but Buffalo 14 did not. (1977,1978) and Dobson (1978) (1976) and has also been found in cattle (Snook et al, 1971): it is thought to be correlated with growth and atresia of anovulatory follicles.…”
Section: Introductionmentioning
confidence: 79%
“…There have been several reports on circulating LH levels during the oestrous cycle in cattle (Bos taurus) (Henricks, Dickey & Niswender, 1970;Snook, Saatman & Hansel, 1971; Madan & Johnson, 1973;Dobson, 1978) and for the zebu (Bos indicus) (Rao, Rao, Rao, Reddy & Rao, 1979). Information on LH concentrations in water buffaloes (Bubalus bubalis), however, is scanty (Heranjal, Sheth, Moodbidri, Desai & Rao, 1976;Sheth, Wadadekar, Moodbidri, Janakiraman & Parameswardan, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…During the bovine oestrous cycle, preovulatory surges of LH and FSH occur simultaneously (Dobson, 1978; and basal plasma concentrations are parallel throughout much of the luteal phase (Rahe et al, 1980;Schallenberger et ai, 1985). However, circulating levels of LH and FSH are clearly divergent during two periods of the oestrous cycle in cattle, suggesting that these times may be critical for ovarian follicular stimulation by appropriate concentrations of each gonadotrophin.…”
Section: Introductionmentioning
confidence: 99%
“…Following luteolysis, increases in basal LH and *Reprint requests to: Dr J. E. Fortune,823 Veterinary Research Tower, Cornell University, Ithaca, New York 14853, USA. LH pulse frequency (Rahe et al, 1980) are accompanied by decreased FSH concentrations (Butler et ai, 1983;Schallenberger et al, 1984). Patterns of LH and FSH also differ early in the luteal phase, when there is a second increase in plasma FSH but there is no concomitant rise in LH (Dobson, 1978;Roche & Ireland, 1981;. There is evidence that a similar secondary 'surge' in FSH is important for development of follicles for the next ovulatory cycle in rats (Grady et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Although further smaller peaks in plasma LH concentrations during the luteal phase have been reported (Schams and Karg, 1969 ;Henricks, Dickey and Niswender, 1970 ;Snook, Saatman and Hansel, 19711, more detailed observations have since shown that, as in other species, episodes of LH secretion occur regularly throughout the cycle and that their frequency and amplitude appear to be dependent on the stage of the cycle (Rahe et al, 1980). A peak in plasma FSH concentrations also occurs at oestrus coinciding with the LH surge (Akbar et al, 1974 ;Schams and Schallenberger, 1976) with a secondary FSH peak of smaller magnitude occurring some 24 h later (Dobson, 1978). Plasma concentrations of oestradiol-170 rise over the four days before oestrus, with a peak occurring on the day before or on the day of oestrus behaviour (Glencross and Pope, 1981 ;Glencross et al, 1981a).…”
mentioning
confidence: 91%